Тактика лікування хворих із мікрокарциномами щитоподібної залози - Бутирський, О. Г.; Астапенко, С. В.; Дубовенко, В. В.; Прокопенко, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2008)
The authors summarize the experience of the thyroid microcarcinomas treatment in the Crimea. They demonstrate increase of intraoperation revealing microcarcinomas that is associated with adequate examination and interpretation of its results and propose differentiated approach to repeated surgery for postponed revealed microcarcinoma without invasion properties.